Effect Of Aegle marmelos on IgM And IgG Antibody Titers in Rattus norvegicus - Prajawanti, Kadeq Novita; Nurdianto, Arif Rahman; Rahmawati, Novia; Negara, Yohanes Ardian Kapri (jitek, 2023)
Aegle marmelos is a traditional plant with many therapeutic benefits; for example, it is used as an immunomodulatory agent. Literature studies reveal many functional and bioactive compounds, such as alkaloids, phenolics, coumarins, flavonoids, terpenoids, and other antioxidants. Based on its chemical content, Aegle marmelos could be an immunomodulatory agent because it can stimulate the production of antibodies against foreign antigens, increasing IgM and IgG. This study aims to determine the effect of Aegle marmelos filtrate on IgM and IgG titers in Rattus norvergicus induced (sheep red blood cells) SRBC 2%. In this study, 30 rats were divided into five groups: negative control received standard diets, positive control received SRBC 2% injection, P1 received SRBC 2% + Aegle marmelos filtrate 25%, P2 received SRBC 2% + Aegle marmelos filtrate 50%, and P3 received SRBC 2% + Aegle marmelos filtrate 75%. The results showed that administration of Aegle marmelos filtrate could increase IgM titers at the highest dose of 75%, although it was not statistically significant. Meanwhile, Aegle marmelos filtrate does not affect IgG titers in SRBC 2% compared to treatment groups.